2011
DOI: 10.3899/jrheum.100089
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Dickkopf-1 Is Correlated with Bone Erosion and Inflammation in Rheumatoid Arthritis

Abstract: DKK-1, as an important mediator, was correlated with bone erosion and inflammation in RA. The change of DKK-1 level may serve as a biomarker of disease activity and bone erosion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
102
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 25 publications
12
102
1
4
Order By: Relevance
“…Furthermore, analysis of musculoskeletal US scanning revealed that DKK-1 levels also showed a highly significant positive correlation with US joint erosions (r=0.718, P<0.001).This was in accordance with Orsolini et al, they reported that patients with erosions had serum levels of Dkk-1 slightly higher than those without erosions [19]. In the present study, there was a highly significant positive correlation between US score of bony erosions and Larsen score (r=0.683, p<0.001).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, analysis of musculoskeletal US scanning revealed that DKK-1 levels also showed a highly significant positive correlation with US joint erosions (r=0.718, P<0.001).This was in accordance with Orsolini et al, they reported that patients with erosions had serum levels of Dkk-1 slightly higher than those without erosions [19]. In the present study, there was a highly significant positive correlation between US score of bony erosions and Larsen score (r=0.683, p<0.001).…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, mean serum Dkk-1 level, in patients was 3165.33 ± 258.441 pg/ml, while it was 1144.44 ± 1028.539 pg/ml in controls. There was a highly significant difference between them (P<0.001).This is in accordance with Orsolini et al, they showed that the mean serum level of Dkk-1 was significantly higher in RA patients than in healthy controls (p<0.001) [19]. In addition, authors previously assessed circulating Dkk-1 levels in patients with active RA compared with patients with OA and healthy individuals.…”
Section: Discussionsupporting
confidence: 86%
“…However, this conclusion is controversial, as others report that NF-κB positively affects osteogenesis (64). Given the central role of Wnt signaling in osteoblast differentiation, the failure of RA focal osteolysis to heal is perhaps more likely due to the osteogenic-suppressive properties of TNF-α mediated through its induction of dickkopf-1 (DKK-1), a potent inhibitor of Wnt activation (65)(66)(67). Interestingly, in contrast to TNF-α arrest, which suppresses osteoclastogenesis but does not increase bone formation, blockade of DKK-1 does both, thus repairing erosive lesions (66).…”
Section: Cytokine-induced Focal Osteolysis In Ramentioning
confidence: 85%
“…DKK-1 and sclerostin (SOST) bind to and inactivate signaling from LRP5/LRP6, 31 inhibiting bone formation. In RA an increase in DKK-1 and SOST has been shown, which blunts OB formation and activity and, together with the increase in bone resorption, is responsible for reduced bone mass 32 and for the formation of articular bone erosions. In fact, DKK-1 levels are associated with an increase in the number of articular erosions independently of age, baseline radiological features, C-reactive protein, or disease activity.…”
Section: Inflammatory Diseases Immune System and Bonementioning
confidence: 99%